Old Berrien Newsletters Vol. 2 No. 1 - Berrien County Historical Foundation (My University, 2008)
The Last Hanging in the Old County Jail The newsletter highlights the tall cupola tower on the southwest corner of the Old Berrien County Jail, built in 1903, which served as the execution site for condemned prisoners via hanging. While the total number of hangings is not recorded, the last two are deemed "most memorable".
Old Berrien Newsletter, Spring 2008.1 electronic record (PDF), 557,537 bytes.
Keywords: Berrien County (Ga.); Periodicals; Newsletters